Hepatobiliary dysfunction in Type-2 diabetes mellitus - Piyush Manoria; Sameer Inamdar; Ravindra Kumar (Journal of Family Medicine and Primary Care, 2017)
Objective: Nonalcoholic fatty liver disease (NAFLD) and gallstones are frequently present in diabetics, but its exact prevalence is not well studied in India. We have done a prevalence study of hepatobiliary involvement in Type-2 diabetes mellitus (T2DM) and also studied the other risk factors of NAFLD. Materials and Methods: Two hundred diabetics and 200 controls underwent anthropometric measurements, abdominal ultrasonography, (USG) and biochemical tests at a tertiary care hospital. Univariate and multivariate logistic regression analyses were done. Results: One hundred and thirty (65%) diabetics and 47 (23.50%) controls were having USG evidence of fatty liver (odds ratio [OR] = 6.046, 95% confidence interval [CI]: 3.904–9.363 [P < 0.0001]). Raised liver enzymes were present in 42 (21%) diabetics and 16 (8%) controls [OR = 3.057, 95% CI: 1.654–5.648 [P < 0.004]). Gallstones were present in 32 (16%) diabetics and 10 (5%) controls (OR = 2.825; 95% CI: 1.850–4.315 P < 0.0001). In addition, waist circumference (WC) and body mass index (BMI) were significantly more in diabetics, but lipid profile was not significantly deranged as compared to controls. Then, all patients with fatty liver were compared with patients with normal liver, and we found that fatty liver group was having raised BMI, WC, liver enzymes, and more dyslipidemia. Multivariate analysis was done which shows the presence of T2DM, elevated liver enzymes, obesity, and elevated WC as independent risk factors of fatty liver. Conclusion: The prevalence of NAFLD and gallstones was higher in diabetics as compared to healthy population. In addition, the presence of T2DM, elevated liver enzymes, obesity, and elevated WC are independent predictors of NAFLD.